LIFELONG LANGUAGE LEARNING IN EUROPE: POSSIBILITIES AND CHALLENGES - Žindžiuvienė, Ingrida; Sruogaitė- Kuliešienė, Austė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Recent demographic changes in Europe (ageing, migration and others) demonstrate the importance of senior adult education – an urgent issue at both national and European Union policy levels. The problem of the research is grounded in the challenges that many European societies currently face: the retirement age being extended, employees need to adapt to the changed working conditions and satisfy urgent demands of the market. The aim of this research is to examine the current situation of senior adult language education in the EU. The research objectives question one of the basic needs faced by senior citizens - to acquire or maintain multilingual skills, without which their status in the competitive market would become complicated. In many European countries, senior adult education is viewed as an integral part of the whole education system that is directed towards engagement of senior citizens into active social life, job maintenance, development of cross-cultural communicative and language skills and more diverse opportunities for self-realization.